2011
DOI: 10.1158/1535-7163.mct-10-0812
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sarcoplasmic/Endoplasmic Reticulum Ca2+-ATPase 2 by Curcumin Induces ER Stress-Associated Apoptosis for Treating Human Liposarcoma

Abstract: Human liposarcoma is the most common soft tissue sarcoma. There is no effective therapy so far except for surgery. In this study, we report for the first time that curcumin induces endoplasmic reticulum (ER) stress in human liposarcoma cells via interacting with sarcoplasmic/endoplasmic reticulum Ca 2þ -ATPase 2 (SERCA2). Curcumin dose-dependently inhibited the cell survival of human liposarcoma cell line SW872 cells, but did not affect that of human normal adipose-derived cells. Curcumin-mediated ER stress vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 26 publications
2
61
0
Order By: Relevance
“…The acceleration of oxidative protein folding by curcumin (10 -50 M) has already been reported (32). Previously, it was reported that curcumin plays an important role in ER stressmediated cellular apoptosis processes, whereby curcumin induces ER stress (35,36). It has also been reported that curcumin (5-10 M) induces ER stress response and protects against oxidative stress in the myogenic C2C12 cell line by increasing levels of the ER chaperon protein, GRP94, which acts as a regulator of calcium homeostasis (36).…”
Section: Discussionmentioning
confidence: 87%
“…The acceleration of oxidative protein folding by curcumin (10 -50 M) has already been reported (32). Previously, it was reported that curcumin plays an important role in ER stressmediated cellular apoptosis processes, whereby curcumin induces ER stress (35,36). It has also been reported that curcumin (5-10 M) induces ER stress response and protects against oxidative stress in the myogenic C2C12 cell line by increasing levels of the ER chaperon protein, GRP94, which acts as a regulator of calcium homeostasis (36).…”
Section: Discussionmentioning
confidence: 87%
“…It has been demonstrated that chronic exposure of b-cells to high glucose resulted in the apoptosis of b-cells (Donath et al 1999, Kim et al 2005, Lablanche et al 2011. In addition, lipotoxicity and ER stress were also the important factors leading to b-cell apoptosis (Choi et al 2007, Sano et al 2009, Wang et al 2011. However, the mechanisms for this factor-associated apoptosis of b-cells have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Under the present experimental conditions, this ratio was clearly altered. Finally, as recent studies have revealed that Ca 2C was also involved in lipotoxicity-and ER stress-induced b-cell apoptosis (Choi et al 2007, Sano et al 2009, Wang et al 2011, the potential role of CREST in these processes was also investigated. Interestingly, ER stress and FFA mimicked the high glucose effects in regard to CREST upregulation and apoptosis induction in cultured b-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were centrifuged at 10,000 rpm for 15 min at 4°C. The supernatant was discarded, and the sediment was dissolved in HBSS buffer and sonicated, and SERCA activity was measured according to the manufacturer's instructions (Nanjing Jiancheng Bioengineering Inst., Nanjing City, China) (30). The kit measures inorganic phosphorus (P i ) content produced from ATPase activity in the samples when ATP is broken down to ADP and P i .…”
Section: Methodsmentioning
confidence: 99%